Particle Size Distribution in the Bottom Sediments of the Kemaman River Estuarine System, Terengganu, Malaysia - B. Y., Kamaruzzaman; N. A. M., Shazili; H., Mohd Lokman (Universiti Putra Malaysia Press, 2002)
Surface sediment samples from the Kemaman River estuarine system were analysed for the grain size in order to understand better the sedimentation processes in the estuary and along the Kemaman river. Their statistical values do not vary significantly according to the seasonal changes but show some relatively lower phi (0) values during the non-monsoon season compared to the monsoon season. The characteristics of deposited sediments at each station are very dependent upon the combination of physical forces such as freshwater runoffs, tidal currents and waves.